2017
DOI: 10.1016/j.jbspin.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory and anti-inflammatory T cells in giant cell arteritis

Abstract: Giant cell arteritis is an autoimmune disease defined by explicit tissue tropism to the walls of medium and large arteries. Pathognomic inflammatory lesions are granulomatous in nature, emphasizing the functional role of CD4 T cells and macrophages. Evidence for a pathogenic role of antibodies and immune complexes is missing. Analysis of T cell populations in giant cell arteritis, both in the tissue lesions and in the circulation, has supported a model of broad, polyclonal T cell activation, involving an array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“… 21 Molecular analysis of the vasculitic lesions has demonstrated that multiple functional lineages contribute to the granulomatous infiltrates and that such functionally lineages are differentially susceptible to therapeutic interventions. 22 Specifically, IL-17-producing T-cells disappear from the lesions in steroid-treated patients, while IFN-γ-producing T-cells persist. 8 , 23 The multi functionality of vessel-wall residing T-cells questions the role of a single antigen in driving the misplaced immune response.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Molecular analysis of the vasculitic lesions has demonstrated that multiple functional lineages contribute to the granulomatous infiltrates and that such functionally lineages are differentially susceptible to therapeutic interventions. 22 Specifically, IL-17-producing T-cells disappear from the lesions in steroid-treated patients, while IFN-γ-producing T-cells persist. 8 , 23 The multi functionality of vessel-wall residing T-cells questions the role of a single antigen in driving the misplaced immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that Th1 cells that produce interferon (IFN)-γ and Th17 cells that produce IL-17 participate in the vasculitic infiltrates (27)(28)(29)(30)(31). An expansion of Th1 and Th17 cells has also been reported for peripheral blood of GCA patients (27,32).…”
Section: Effector Cd4 + T Cellsmentioning
confidence: 99%
“…Removing the PD‐1/PD‐L1–dependent protection lead to a dense T cell infiltrate, with T cells from multiple different lineages represented (Fig. ).…”
Section: Insufficiently Suppressed T Cells In Gcamentioning
confidence: 99%
“…Cellular origins and processes giving rise to the growing intima are not entirely clear, but proceed at rapid pace in GCA . Arteries treated with the checkpoint inhibitor had markedly increased numbers of microvessels and the thickness of the intimal layer doubled . It is possible that removing negative signaling by PD‐1 blockade translated into much more aggressive inflammation, equally intensifying downstream events.…”
Section: Insufficiently Suppressed T Cells In Gcamentioning
confidence: 99%